Copy number amplification of TTPAL promotes cholesterol biosynthesis and esophageal squamous cell carcinoma progression via elevating NSUN2-mediated m5C modification of SREBP2 mRNA - Shan Huang; Yuanyuan Liu; Manyu Zhao; Tao Wang; Lihua Mao; Ting Wang; Chunyuan Guo; Wentao Huang; Zimei Peng; Zhen Zhang; Rui Jiang; Xinrui Ma; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Alterations in copy number are crucial genetic events in the development of esophageal squamous cell carcinoma (ESCC). Here, we show that Tocopherol alpha transfer protein-like (TTPAL) is highly amplified and frequently overexpressed in human ESCC. Using Ttpal-KO mouse mode, we demonstrate that TTPAL promotes ESCC cell proliferation and accelerates tumor development by driving cholesterol biosynthesis. Mechanistically, TTPAL upregulates a key transcription factor in cholesterol biosynthesis-sterol regulatory element-binding transcription factor (SREBP2) in ESCC cells. TTPAL interacts with the RNA methyltransferase NSUN2 and relieves the ubiquitination of NSUN2, protecting NSUN2 from proteasome-mediated degradation. In turn, NSUN2 catalyzes the m5C modification of SREBP2 mRNA, and then the m5C modified SREBP2 mRNA binds to the m5C reader protein-ALYREF to enhance its stability, thereby increasing SREBP2 expression. Moreover, we validate the efficacy of cholesterol biosynthesis inhibitor simvastatin in ESCC with high TTPAL expression. Overall, our results uncover a novel function of TTPAL in regulating SREBP2 expression, revealed a previously unknown TTPAL/NSUN2/SREBP2 pathway that promotes cholesterol biosynthesis in ESCC cells, and identified sensitively to cholesterol biosynthesis inhibitor simvastatin.